Edukasi Kesehatan Lingkungan Dalam Meningkatkan Pengetahuan Dan Perilaku Pengelolaan Sampah Domestik - Isti Mulyawati (Indonesian Journal of Health Community, 2026)
Household waste management in rural areas remains an important environmental issue, particularly due to the low level of public knowledge, attitudes, and behavior regarding proper waste management. This study aimed to analyze the effect of waste management counseling on community knowledge, attitudes, and behavior in household waste management in Merbuh Village, Singorojo District, Kendal Regency. The study employed a quantitative approach using a one group pretest-posttest design. The sample consisted of 94 respondents selected through simple random sampling. Data were collected using questionnaires, observations, and documentation. Data analysis was conducted using validity tests, reliability tests, paired sample t-test, and N-Gain analysis. The results showed that all variables experienced improvement after the counseling intervention, with a significance value of 0.000 (p < 0.05). The N-Gain results indicated an increase in knowledge of 0.6 (moderate category), attitude of 0.8 (high category), and behavior of 0.9 (high category). This study concludes that household waste management counseling has a positive and effective influence on improving community knowledge, attitudes, and behavior. The contribution of this study lies in strengthening community-based educational models as a strategy to improve household waste management in rural areas.